2014
DOI: 10.2174/18715273113126660135
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Linkages Between Diabetes and Alzheimer's Disease: Current Scenario and Future Prospects

Abstract: After the revolutionary Rotterdam study that suggested there was an increased risk of developing Alzheimer's disease (AD) in patients with type-2 diabetes mellitus (T2DM), a number of studies have provided direct evidence for the linkage between AD and T2DM. In recent years, AD is considered as a neuroendocrine disorder, also referred as type-3 diabetes. There is a growing list of evidence to suggest that, in addition to impaired insulin signaling, there are a number of additional factors that may act as mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 1 publication
1
25
0
Order By: Relevance
“…Insulin resistance in T2DM causes mitochondrial dysfunction, which in turn triggers inflammation response [82, 83]. In these conditions, insulin resistance increases the levels of cytokines such as IL-6, IL-1β and IL-18, tumor necrosis factor-alpha (TNF-α), alpha-1-antichymotrypsin and C-reactive protein [8486].…”
Section: Inflammation and Admentioning
confidence: 99%
“…Insulin resistance in T2DM causes mitochondrial dysfunction, which in turn triggers inflammation response [82, 83]. In these conditions, insulin resistance increases the levels of cytokines such as IL-6, IL-1β and IL-18, tumor necrosis factor-alpha (TNF-α), alpha-1-antichymotrypsin and C-reactive protein [8486].…”
Section: Inflammation and Admentioning
confidence: 99%
“…It has been suggested that AD and T2DM result from various metabolic abnormalities and defective insulin metabolism. Shared pathology, metabolic profiles, transcriptomics, and proteomics are the possible links between these two diseases . Insulin signaling abnormalities could be the underlying mechanism affecting the outcome of AD; insulin resistance and disordered degradation of amyloid seem to link diabetes mellitus with AD .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the absence of negative feedback control of acetylcholine, the decrease of AChE concentration leads to an increase of interleukin-1 (IL-1) and tumor necrotic factor (TNF-α). Therefore, the observation that the actions of AChase and BChase are increased in the plasma and red blood cells of T2DM and AD patients suggests that these proteins may be possible biochemical markers of these diseases (Dar et al, 2014).…”
Section: Figure 2 Molecular Mechanisms Underlying Long-term T2dm Inmentioning
confidence: 99%